The Relationship Between Women and Men in the Qur'an: A Structural Critical Analysis by Levi-Strauss - Niat, Khoirun (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2024)
This study applies Claude Lévi-Strauss's structuralist methodology to analyze Qur'anic narratives featuring women and their male counterparts, examining 42 female figures across 28 stories from 15 surahs to reveal an equilateral triangular deep structure defined by three invariant mythemes: complementarity (e.g., Ḥawwā’-Ādam functional synergy), substitution (e.g., Hājar's autonomous replacement of Ibrāhīm; Maryam's parthenogenetic child-rearing), and opposition (e.g., Āsiyah-Pharaoh tauḥīd/taghuṭ tension). Employing qualitative hermeneutic phenomenology with syntagmatic-paradigmatic decomposition—systematic extraction from Uthmānic recension via Tafsīr al-Jalālain, emic binary opposition identification, etic bundle analysis, and Proppian morphology—the research uncovers non-hierarchical gender dynamics manifesting waḥdat maudū‘iyyah as tawḥīd microcosm, where women exhibit full relational agency transcending patriarchal determinism. Findings challenge traditional tafsīr, affirming equilateral narrative weight across vectors and supporting contextual reinterpretation of qawwāmūn (QS 4:34). Methodological rigor includes intercoder reliability, thick description validation across qirā'āt, and commutative testing for structural invariance. Implications extend to computational themes tylometry, maqāṣid al-sharī‘ah gender exegesis, and comparative Abrahamic mythology, enriching contemporary Islamic feminist discourse.